Los trabajadores extranjeros en la provincia de Zaragoza - Escalona Orcao, Ana Isabel; Escolano Utrilla, Severino (Geographicalia, 2017)
This article comprises the first results of a piece of research on foreign workers in the province of Zaragoza, we have carried out in the context of international migration in Europe and Spain. Now, we are publishing our findings and conclusions on different aspects related to the laboral activity of inmigrants: the number of workers, the professional skill, segregation within activities and occupations, specialisation according to nationalities and the locational patterns in the province.